S-Wave Attenuation Variation and its Impact on Ground Motion Amplitudes During 2016–2017 Central Italy Earthquake Sequence - Akinci, Aybige; Munafò, Irene; Malagnini, Luca (Frontiers in Earth Science, 2022)
A very energetic seismic sequence struck the central Apennines, Italy, in 2016–2017, with a series of damaging earthquakes, three of them with moment magnitudes M ≥ 5.9, and five of them with M ≥ 5.0, occurred over a few months between 24 August 2016, and late 2017. Several studies explained the phenomenon of a cascading earthquake sequence with fluid movements that provoked the rupture of different parts of the fault segments at different times and locations (e.g., Miller, Nature, 2004, 427, 724–727; Gabrielli, Frontiers in Earth Science, section Structural Geology and Tectonics, 2022; Malagnini, Frontiers in Earth Science, section Solid Earth Geophysics, 2022). In this study, we investigated the variation of crustal S-wave attenuation in terms of the frequency-dependent quality factor Q(f) before and after the main events (including the Amatrice, Visso, and Norcia sub-sequences, hereafter, AVN, and periods before and after the AVN multi-mainshock sequence). The spectral characteristics of regional attenuation in the central Apennines, as well as of the earthquake sources of the AVN sequence, are derived through regression analysis using a large set of seismograms; Q(f) is modeled, together with the bilinear geometrical spreading, g(r), using a widely used tool, namely, random vibration theory, RVT (Cartwright and Longuet-Higgins, 1956). The primary objective of this effort was to examine how the variability of crustal anelastic attenuation would impact the earthquake-induced ground motions. The latter is quantified in terms of peak ground accelerations (PGAs), peak ground velocities (PGVs), and pseudo spectral accelerations (PSAs) at 0.3 and 2 s . Here, we showed that the main events of the AVN sequence strongly affect crustal S-wave attenuation, including its frequency dependence. However, the effects of 1/Q(f) fluctuations on earthquake-induced ground motions are small and have a negligible impact on the seismic hazard.